Dilemma in localising international law in the drafting process of Thailand's human rights action plan. Issue 4 (19th May 2021) - Techagaisiyavanit, Wanaporn; Chokprajakchat, Srisombat
ABSTRACT: The Vienna Declaration 1993 is an important instrument that provides a platform for creating a national human rights plan. This paper focuses on the practical aspect of localising international law in the drafting process of Thailand's human rights action plan. It argues that while the drafting process can serve as an argument against the existing criticism concerning the "supra-national" character of international law in the alienation of the local participation, the process also gives rise to the dilemma of public participation, which the paper calls "a national standardisation" on important human rights issues, namely the rights to social welfare of migrant workers and their dependants, and the abolition of capital punishment.